Professional deontology and medical practice in prisons - J. García-Guerrero; E.J. Vera-Remartínez
Objective: To study the knowledge on professional deontology amongst doctors in prisons. Materials and Method: Descriptive, transversal and multi-centre study. Labour, collegiate, social, demographic and deontological variables were collected. A descriptive analysis of the variables was performed. A bivariate analysis was made by binary logistic regression models, attending to the odds ratio, and assuming a 95% confidence interval. Data was processed by SPSS v.20 software. Results: 118 doctors replied. 68 men (57.6%), with an average age of 51 years (50-53). 100 know about the Deontology Committee (84.7%), but just 77 (65.3%) know its functions properly. 42 (35.6%) know about the existence of the Deontological Code, and 37 (31.3%) have read and apply it. Those who made a correct definition of deontology do find more deontological issues in their daily work [23(46.9%) vs. 18(26.1%); OR: 2.506; IC95%: 1.153-5.451; p=0.020] and would denounce a colleague more often to the Medical Association [40(81.6%) vs. 42 (60.9%); OR: 2.857; IC95%: 1.197-6.819; p=0.018]. Older ones know more about the deontology commissions' functions [54(73%) vs. 23(52.3%); OR: 2.465; IC95%: 1.127-5.394; p=0.024] and have already denounced situations to the Medical Association [27(36.5% vs. 5(11.4%); OR: 4.481; IC95%: 1.577-12.733; p=0.005], but think that a different Care Ethics Committee is unnecessary [57(77%) vs. 42(95.5%); OR: 0.160; IC95%: 0.035- 0.729; p=0.018]. Conclusions: Prison doctors know little about what professional deontology really is. This knowledge increases with age in the profession and is associated with an increased perception of deontological issues in daily practice.